Metode Pilates Untuk Penurunan Kecemasan Ibu Hamil Pertama Trimester III - Purwanti, Dwi Surya (ANFUSINA: Journal of Psychology, 2020)
This research set out to investigate the effect of pilates method to reduce anxiety for pregnant women, especially in third trimester. Hypothesis proposed: there is anxiety difference for pregnant women in third quarter between control group and experimental group. Subject of research contains pregnant women who check their pregnancy at private childbirth clinic in Yogyakarta. On the basic of medical record data, it was obtained that eight pregnant women meeting research criteria, that was: first pregnancy and entered third trimester data collection methods used were personal quesioner, pregnancy anxiety scale. Analysis technique used U Mann – Whitney test. To see the differences of anxiety condition before and after treated with Pilates method in experimental group, Wilcoxon Rank Test was used. As results, it has been shown that (Z = -1.964; p < 0.05). Experimental group’s anxiety level is lower (mean = 62.33) than control group’s anxiety level (mean = 100.33). Experimental group, in particular, has been proved that movements in Pilates method for pregnancy were effective in reducing anxiety in facing first pregnancy in third trimester (t = 7.821; p < 0.05) with mean before = 95.00; mean after = 62.33.  So pilates method effective to reduce anxiety for pregnant women in third trimester.